2011
DOI: 10.1063/1.3559490
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature ferromagnetism in HfO2 films

Abstract: HfO2 films were produced by sputter deposition in the substrate temperature (Ts) range of room temperature (RT)−300 °C and their structural, magnetic, and electrical properties were evaluated. The results indicate that the HfO2 films crystallize in the monoclinic structure and are oriented along the (−111) direction. Magnetization measurements (300–1.8 K) evidence their RT ferromagnetism. The effect of Ts is significant on the magnetic moment (M) and coercivity (Hc). M and Hc values enhanced with increasing Ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In a previous theoretical study we showed how the activation energy for small hole polaron diffusion in m-HfO 2 is rather low, 0.14 eV, consistent with the high temperature conductivity observations [51]. There has also been some speculation on the possible role cation vacancies may play in explaining observed ferromagnetism [31][32][33]35]. However, DFT calculations for m-HfO 2 employing local or semilocal functionals found relatively weak ferromagnetic coupling between cation vacancies insufficient to explain experimental observations [34,52].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a previous theoretical study we showed how the activation energy for small hole polaron diffusion in m-HfO 2 is rather low, 0.14 eV, consistent with the high temperature conductivity observations [51]. There has also been some speculation on the possible role cation vacancies may play in explaining observed ferromagnetism [31][32][33]35]. However, DFT calculations for m-HfO 2 employing local or semilocal functionals found relatively weak ferromagnetic coupling between cation vacancies insufficient to explain experimental observations [34,52].…”
Section: Introductionsupporting
confidence: 73%
“…One such example is provided by hafnium dioxide (HfO 2 ), a material which finds a number of applications in microelectronics [26,27]. It has been suggested that cation vacancies can induce high temperature p-type conductivity [28][29][30] and contribute to the so far unexplained ferromagnetism in HfO 2 [31][32][33][34][35]. However, our knowledge of the fundamental electronic and magnetic properties of cation vacancies in HfO 2 remains extremely limited, presenting an obstacle to deeper understanding of these complex effects.…”
Section: Introductionmentioning
confidence: 99%
“…The crossing point of the ZFC and FC curves in UiO-66­(Hf) can be observed at approximately 270 K, above which the paramagnetic behavior is dominant. The existence of d 0 ferromagnetism in HfO 2 thin films has been reported by several authors. ,, In the case of UiO-66­(Hf), the source of magnetism can also be Hf 4+ with oxygen vacancies. However, ferromagnetic behavior in UiO-66­(Hf) has been observed only at low temperatures.…”
mentioning
confidence: 89%
“…The existence of d 0 ferromagnetism in HfO 2 thin films has been reported by several authors. 32 , 44 , 45 In the case of UiO-66(Hf), the source of magnetism can also be Hf 4+ with oxygen vacancies. However, ferromagnetic behavior in UiO-66(Hf) has been observed only at low temperatures.…”
mentioning
confidence: 99%
“…These dielectrics have extensively been investigated and are being used as gate oxides in scaled complementary metal oxide semiconductor (CMOS) and storage capacitors of dynamic random access memory (DRAM) devices [8][9][10]. Moreover, due to their outstanding electronic, optical and mechanical properties, high dielectric constant, and wide bandgap, HfO 2 based materials are also being actively investigated in several other industrial applications [11][12][13]. Nevertheless, beside few demonstrations of inversion mode III-V metal oxide semiconductor field effect transistors (MOSFETs) [14][15][16], there is a lack of information on the integration and potential use of the high-K-based dielectrics in III-V based electronic and optoelectronic components.…”
Section: Introductionmentioning
confidence: 99%